Effect of intravenous infusion of atriopeptin 3 on immediate renal allograft function. - Ratcliffe, P; Richardson, A; Kirby, J; Moyses, C; Shelton, JR; Morris, P (1991)
Thirty-eight recipients of nineteen pairs of cadaveric kidneys were entered into a double-blind randomized study in which one recipient received a 12-hour intravenous infusion of Atriopeptin III (AP-3), a synthetic analogue of atrial natriuretic factor, commencing at release of the vascular clamps, and the other received a placebo infusion. In an initial dose ranging study, successive groups of six kidneys (3 pairs) were randomized to receive each of 0.0125, 0.025, 0.05 micrograms/kg/min AP-3 or placebo. Thereafter 20 kidneys (10 pairs) received 0.1 micrograms/kg/min or placebo. There was no discernable effect of AP-3 on allograft creatinine clearance or sodium excretion either when the highest dose of AP-3 was considered alone or when all doses were considered together. Averaged creatinine clearance over the period 0 to 24 hours after transplantation was 20.1 +/- 14.7 ml/min in patients receiving active treatment and 18.2 +/- 13.7 ml/min in those receiving placebo. Thus, despite the documentation of a protective effect of atrial natriuretic factor in animal models of renal ischemia, it is unlikely that intravenous infusion of AP-3 in this dose range will be of benefit in improving immediate renal allograft graft function.